Study of morphological characteristics of several valuable Armeniam varieties of tomato - Vardanyan V.A.; Kirakosyan G.V.; Simonyan R.K.; Sarikyan K.M. (E3S Web of Conferences, 2024)
The article presents the researches on the morphological characteristics of seedlings, plants and fruits of several valuable Armenian tomato varieties intended for fresh consumption: Lia, Titan, Orange, intended for processing Marine and chery Zeytun, in the hot conditions of the Ararat Plain. The results of the study showed that the investigated varieties of tomato are distinguished from each other by morphological characteristics of plants, fruits of different size, shape, color, they are adaptive in the case of cultivation in the hot climatic conditions of the Ararat Plain. The results of the study allow to guarantee the cultivation of these new cultivars Titan, Orange, Marine, Zeytun in the farms of the zones with similar conditions.